Oz - The Fourth Season Episode 1-16 - Bernstein, Adam; Fink, Kenneth; Gajic, Goran; Zakrzewski, Alex; Acevedo, Kirk; Hudson, Ernie; Moreno, Rita (Oz - The Emerald City Collection, 2009)
At Oswald State Correctional Facility, Level Four, the wish list inside Emerald City keeps growing. Ryan O'Reily wants revenge on a TV newsman who slandered him years ago. Miguel Alvarez wants out of solitary confinement after tasting freedom briefly. Agamemnon Busmalis wants to hear wedding bells. Vern Schillinger wants Kareem Said dead, by any means possible. In "Oz", be careful what you wish for ... you might just get it. [www.play.com]